Proceeding of the international workshop on the impact of weather parameters on grownth and yield of rice, 7-10 April 1986 (Los Banos, Philippines, 1987)
The book provides a reliable and timely, yet inexpensive, weather-based informationsystem that will continuously monitor and assess the impact of weather (such as drought, floods, typhoons, etc.) on rainfed agriculture
Keywords: Crops and climate,Rice climatic factors